2020
DOI: 10.1186/s12947-020-00193-3
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term effect of balloon aortic valvuloplasty on mitral regurgitation in aortic stenosis

Abstract: Background: Balloon aortic valvuloplasty (BAV) offers an alternative to conventional aortic valve replacement in elderly and frail patients with severe aortic stenosis (AS) for whom there are no other effective options. We aimed to investigate the mid-term effect of BAV on mitral regurgitation (MR) in patients with severe AS. Methods: Our analysis was based on the data from 83 patients with severe AS (mean age, 86 ± 5 years; female, 68) treated using BAV. Echocardiography was performed before the procedure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The potential beneficial effect of BAV in AS patients with concomitant MR is provided by the reduction of LV afterload, which may lead to cascading haemodynamic effects such as a reduction of LV filling pressure, transmitral systolic gradient, and reverse remodelling of the LV along with improved mitral valve geometry (Figure 1) [9][10][11]. This is in line with the results of Masaki et al showing that the haemodynamic changes are favourable irrespective of MR aetiology, but the reduction of LV volume seems to confer a greater advantage in type I and IIIb according to Carpentier's classification [12]. Therefore, since BAV may exert a favourable effect mainly in functional MR, the echographic evaluation of mitral valve anatomy and mechanics is of paramount importance.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The potential beneficial effect of BAV in AS patients with concomitant MR is provided by the reduction of LV afterload, which may lead to cascading haemodynamic effects such as a reduction of LV filling pressure, transmitral systolic gradient, and reverse remodelling of the LV along with improved mitral valve geometry (Figure 1) [9][10][11]. This is in line with the results of Masaki et al showing that the haemodynamic changes are favourable irrespective of MR aetiology, but the reduction of LV volume seems to confer a greater advantage in type I and IIIb according to Carpentier's classification [12]. Therefore, since BAV may exert a favourable effect mainly in functional MR, the echographic evaluation of mitral valve anatomy and mechanics is of paramount importance.…”
supporting
confidence: 83%
“…This is in line with the results of Masaki et al . showing that the haemodynamic changes are favourable irrespective of MR aetiology, but the reduction of LV volume seems to confer a greater advantage in type I and IIIb according to Carpentier’s classification [ 12 ]. Therefore, since BAV may exert a favourable effect mainly in functional MR, the echographic evaluation of mitral valve anatomy and mechanics is of paramount importance.…”
mentioning
confidence: 99%
“…The data on MR reduction after BAV are limited. In a study by Masaki et al a significant reduction of MR was observed at 1 month and 3 months after the procedure, with the change at 1 month in the LVESD and MR jet area being predictive of persisting significant MR at 3 months after BAV [ 21 ]. Maluenda et al found that nearly half of the patients with severe AS and coexistent MR showed improvement in the magnitude of MR after BAV [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…All together, these data suggest that it is currently difficult to estimate MR change in individual patients because there are no randomized trials, and no evidencebased guidelines about whether MR should be addressed during SAVR or TAVR. Balloon aortic valvuloplasty has been shown to reduce the severity of MR in nearly half of patients with severe AS and coexistent MR [62,63]. However, there is no evidence to support the regular use of this procedure to identify patients who do not need a second mitral procedure during AVR.…”
Section: The Effects Of Valve Replacement For Aortic Stenosis On Mitral Regurgitationmentioning
confidence: 99%